Technology for Preventing the Wax Deposit Formation in Gas-Lift Wells at Offshore Oil and Gas Fields in Vietnam - Mikhail Konstantinovich Rogachev; Thang Nguyen Van; Aleksandr Nikolaevich Aleksandrov (Energies, 2021)
Within the past few decades, the production of high-wax oils at offshore fields in Vietnam has been fraught with severe problems due to the intense formation of asphalt-resin-paraffin deposits (ARPD) in the downhole oil and gas equipment. The formation of organic wax deposits in the tubing string led to a significant decrease in gas-lift wells production, efficiency of compressor units, transport capacity of the piping systems, along with an increase in equipment failure. Subsequently, the efficiency of gas-lift wells dramatically decreased to less than 40% as a whole. The existing methods and technologies for combating organic wax deposit formation in downhole equipment have many advantages. However, their use in producing high-wax anomalous oil does not entirely prevent the wax formation in the tubing string and leads to a significant reduction in oil production, transport capacity, and treatment intervals. The results of theoretical and experimental studies presented in this article demonstrate that a promising approach to improve the efficiency of gas-lift wells during the production of high-wax oil is to use the technology of periodic injection of hot associated petroleum gas (APG) into the annulus of an oil-producing well. The effectiveness of the proposed method of combating wax formation in gas-lift wells highly depends on the combination of a few factors: the determination of wax deposit formation intensity in the well and the implementation of a set of preparatory measures to determine the optimal injection mode of hot APG (flow rate and injection depth) into the annulus between tubing strings and technological pipes. The injection depth of the hot APG should not be less than the depth of wax formation in the tubing string. The optimal injection rate of hot APG is determined by analyzing and mathematically modeling the APG injection system based on well-known thermodynamic laws.